Association Between Cholecystectomy and Gastric Cancer Risk: A Systematic Review and Meta-Analysis - Yang, Ying; Liu, Ming-Hua; Li, Yan (Frontiers in Oncology, 2022)
Objectives Although several epidemiological studies have attempted to evaluate the relationship between cholecystectomy and gastric cancer risk, the findings have been controversial. This study aimed to carry out a systematic review and meta-analysis following the reporting guidelines to comprehensively analyze and quantify the evidence of the aforementioned association. Methods Studies were identified by searching the Medline (PubMed), Embase, and Web of Science from inception to November 30, 2020, with only studies published in English being considered. Summary relative risks (RRs) and 95% confidence intervals (CIs) were calculated by random-effects models. Results Eight studies (five cohort studies and three case–control studies) with a total of 26,063 gastric cancer patients and 848,081 participants were included. The summarized RR of the relationship between cholecystectomy and gastric cancer risk was 1.11 (95%CI: 1.03–1.20), with low heterogeneity (P = 0.117, I2 = 37.8%). These positive findings were consistent in most subgroup analyses like region in Asia, number of cases ≥200, cohort study design, sex in male, low risk of bias, exposure collection by database, and adjustments made for age, gender, calendar year. Of note, we also observed positive association between cholecystectomy and non-cardia of gastric cancer risk (RR = 1.17, 95%CI: 1.04–1.33). No publication bias was present. Conclusions The aforementioned evidence suggested that a history of cholecystectomy was associated with a slightly elevated risk of gastric cancer. Results of most subgroup analyses also supported the main findings. More prospective studies are warranted to further validate these findings.